PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KLINIK KECANTIKAN CORPODERMA RUMAH SAKIT KELUARGA SEHAT PATI - Sutiyana, 08.3502.0725; Budi Setyawan, Mulyo (Students Journal of Economic and Management, 2012)
In making a purchase, consumer behavior is influenced by several factors, including factors of product quality and service quality. Related to this study sought to determine the factors whichdetermine consumer decisions in the conduct of research, especially related to the quality factor of the product and service quality, which one of these factors to be the most dominant factor in the purchasing decision. The population in this study were respondents or consumers who are patients of the Clinic Beauty Corpoderma Starch. The sampling technique used in this study was purposive sampling sanpel selection based on certain criteria, namely the number of patients accounted for 4015 of the years 2007-2011, to determine the number of samples used Slovin formula. So the number of samples to be used dala study is a minimum of 100 respondents. Which in this study used sampling techniques with accidental sampling the individual who placed the study found. Based on the results of analysis using multiple linear regression test is known that there is a positive and significant relationship between the quality of the product (X1) with the purchase decision (Y), there is a positive and significant relationship between quality of service (X2) with the purchase decision (Y). Based on the analysis of the coefficient of determination factor variables influence the quality of the product (X1) and the variable quality of service (X2) jointly influence the purchase decision variable (Y) is equal to 79.9% while the remaining 20.1% is influenced by other variables not included in this study.Key words : Quality Product,Quality Service, dan Purchase Decision.